Perfect selective metamaterial absorber with thin-film of GaAs layer in the visible region for solar cell applications - Kumar R.; Singh B.K.; Tiwari R.K.; Pandey P.C. (My University, 2025)
In this paper, we have presented a new design of a metamaterial perfect absorber (MPA) consisting of three layers of metal-dielectric-metal in which the top layer is considered of special kind square patches at different places in a unit cell. This MPA exhibits wideband, wide-angle, and polarization-independent absorption performance in the visible region. The proposed MPA structure is composed of a resonator of metal and spacer of a dielectric layer. The interactions between the resonator and the coupling of metal-dielectric create the plasmonics effects which are responsible for the perfect absorption. Under a specific condition, this simulated absorber structure exhibits an extremely high broadband absorption between 591.54 and 704.40 nm wavelength range with near-unity absorption, and a single peak observed at 385.33 nm with the absorption of 94.16%. We extracted the impedance of the absorber and matched it with free space, and also demonstrated the effective permittivity and permeability. Moreover, the parametric study of the resonators, dielectric layer, and multi-band topology has also been investigated. The polarization-insensitive-based metamaterial may be utilized to improve the efficiency of different devices in the visible range. Furthermore, we have calculated the absorption of the proposed MPA under solar radiation (AM1.5) for different structural parameters. The proposed absorber greatly enhances the conversion efficiency which is highly useful for solar cells. We also determined the short circuit current density of this absorber for different thicknesses of the GaAs layer. The meta-surface of Al metal provides a good performance in comparison to other costly metals and the proposed structure may be used for different devices. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.